An American soldier in World War I - Browne, George, 1894- (Studies in war, society, and the military., 2006)
"George "Brownie" Browne was a twenty-three-year-old civil engineer in Waterbury, Connecticut, when the United States entered the Great War in 1917. He enlisted almost immediately and served in the American Expeditionary Forces until his discharge in 1919. An American Soldier in World War I is an edited collection of more than one hundred letters that Browne wrote to his fiancee, Martha "Marty" Johnson, describing his experiences during World War I as part of the famed 42nd, or Rainbow, Division."--Jacket